Addition of Tibial Tubercle Osteotomy to Combined MPFL Reconstruction and Lateral Retinacular Release not Recommended for Recurrent Patellar Dislocation in Patients with 15 to 20 mm TT-TG - Zhang, Yuankai; Nan, Kai; Zhao, Yan; Zhang, Xin; Song, Qichun; Fan, Lihong; Shi, Zhibin; Dang, Xiaoqian (The Journal of Knee Surgery, 2022)
Surgery is the primary treatment for recurrent patellar dislocation. However, there is still a lack of consensus regarding the choice of combined surgical methods due to the complexity of the anatomical factors. This study aimed to investigate the efficacy and radiological changes in medial patellofemoral ligament reconstruction (MPFLR) and lateral retinacular release (LRR) with and without tibial tubercle osteotomy (TTO) for recurrent patellar dislocation in patients with a tibial tubercle-trochlear groove (TT-TG) distance of 15 to 20 mm. Fifty-four patients were enrolled in this retrospective study between 2010 and 2014. The average patient age was 21.6 ± 5.0 years. All patients underwent MPFLR and LRR, and in 18 patients, these procedures were combined with TTO. Patients were evaluated preoperatively and postoperatively for patellar lateral shift, patellar tilt angle, TT-TG distance, Q-angle, Caton–Deschamps index (CDI), Kujala, and Lysholm scores. The minimally clinical important difference was used to compare clinical outcomes between two groups. In the mean follow-up of 82.6 ± 15.9 months, functional scores improved significantly in both groups (p < 0.01). There were no significant differences in postoperative function scores between the two groups (Kujala, p = 0.25, mean difference = 1.5, 95% confidence interval [CI]: –1.4–4.4; Lysholm, p = 0.76, mean difference = –0.6, 95% CI: –5.9–4.7). Additionally, TTO significantly decreased Q-angle (23.6 ± 2.4 vs. 17.4 ± 2.9, p < 0.01), TT-TG (17.1 ± 1.5 vs. 10.4 ± 1.8, p < 0.01), and CDI (1.18 ± 0.12 vs. 1.08 ± 0.07, p < 0.01). Combined MPFLR and LRR with and without TTO are both effective techniques for recurrent patellar dislocation. Additional osteotomy can correct patellar alta and tibial tubercle lateralization. However, given that there were no significant differences in postoperative functional scores or recurrence rate between groups, we may not recommend TTO in addition to MPFLR and LRR in patients with TT-TG of 15 to 20 mm. Long-term and prospective cohort studies are required to assess further outcomes.
Keywords: patellar dislocation; tibial tubercle osteotomy; TT-TG; medial patellofemoral ligament reconstruction; lateral retinacular release